Analysis of Constraints and Challenges in the Use of ChatGPT for Students’ Scientific Writing - Hijrah Purnama Sari Ariga; Alfi Syahrin; Wirdatul Isnani (English Language Teaching Prima Journal (ELT), 2026)
The purpose of this research is to analyze the limits and obstacles faced by the seventh-semester students of Universitas Almuslim in using ChatGPT for scientific writing. A qualitative descriptive technique was adopted to achieve in-depth understanding of students’ experiences and perceptions. The data were obtained from semi-structured interviews and open-ended surveys with 25 seventh-semester students who utilized ChatGPT for academic writing. Data collected were analyzed using theme analysis. The findings identified four significant themes: concerns over authenticity and trustworthiness of information, ethical concerns around academic integrity, over-reliance on AI-generated content and diminished critical involvement, and difficulty in crafting effective prompts. Most participants viewed ChatGPT as a beneficial tool that improved writing speed and assisted the writing process, but they emphasised the significance of fact-checking the information supplied by the AI and using the technology responsibly. The results indicate that the successful use of the ChatGPT in scientific writing is not only dependent on the technology itself, but also on students’ critical thinking, digital literacy, and ethics awareness. This study adds to the literature on generative AI in higher education and underscores the need for explicit institutional standards and AI literacy training to facilitate the appropriate usage of AI-assisted writing tools.